2013
DOI: 10.1007/s00213-013-3074-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and memory: The influence of drink, expectancy, and beliefs

Abstract: The findings indicate that expectancy effects are unlikely to be confused with glucose enhancements, but beliefs about consuming glucose can augment performance on delayed free recall. The discussion considers the hippocampus and complexity hypotheses of glucose's mode of action and proposes the routine collection of drink beliefs in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…No task improvements were observed when participants thought that they were consuming aspartame. Similar effects were observed by Stollery and Christian [33] who found a subtle improvement in a task of delayed free recall when participants believed they had consumed glucose. Whilst the authors concluded that the expectancy effects were small and unlikely to be confused with glucose enhancements, they did suggest that routine collection of product beliefs should be carried out in future studies.…”
Section: Expectancy and Placebo Effectssupporting
confidence: 85%
“…No task improvements were observed when participants thought that they were consuming aspartame. Similar effects were observed by Stollery and Christian [33] who found a subtle improvement in a task of delayed free recall when participants believed they had consumed glucose. Whilst the authors concluded that the expectancy effects were small and unlikely to be confused with glucose enhancements, they did suggest that routine collection of product beliefs should be carried out in future studies.…”
Section: Expectancy and Placebo Effectssupporting
confidence: 85%
“…Following consent, participants had their blood glucose measured (pre-session) using the OneTouch Ultra blood glucose monitoring system (donated by Johnson & Johnson Company) and then received their allocated drink (glucose or placebo). While they waited 10 min to allow blood glucose levels to rise (Meikle et al 2004 ; Stollery and Christian 2013 ), demographic information was collected (e.g. age, sex, BMI, fasting compliance) and they completed a stress-arousal checklist (Mackay et al 1978 ) to evaluate whether stress or arousal changes mediate the effect of glucose on performance (see Meikle et al 2004 ; Smith et al 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, based on the composite scores that incorporate performance on this spatial memory task, glucose either did not influence performance (Scholey and Kennedy 2004 ) or produce impairment (Jones et al 2012 ). Stollery and Christian ( 2013 ) also only examined location memory by presenting identical objects (circles) at random locations in a 9 × 9 grid and assessing recognition memory for exact locations. Although location memory declines substantially as the number of objects to remember increases, neither speed or accuracy varied with the 50 g glucose dose given.…”
mentioning
confidence: 99%
“…Despite the intuitive appeal of the serotoninergic hypothesis and the literature reporting CHO effects on several mood aspects, there are also studies investigating CHOmood interactions that have reported conflicting findings. Over the last three decades, an increasing number of empirical reports have suggested that ingestion of CHOs does not lead to any pronounced increases in subjective mood and overall affect, but can even have detrimental effects on mood (Adan and Serra-Grabulosa, 2010; Brody and Wolitzky, 1983;Duckworth et al, 2013;Giles et al, 2012;Harte and Kanarek, 2004;Howard and Marczinski, 2010;Jones and Sünram-Lea, 2008;Meikle et al, 2004;Miller et al, 2013Miller et al, , 2014O'Neal et al, 2013;Owen et al, 2013;Qin et al, 2017;Hammersley, 1998, 1995;Riby et al, 2004;Scholey et al, , 2009Scholey and Fowles, 2002;Scholey and Kennedy, 2004;Seo et al, 2014;Stollery and Christian, 2013;Sünram-Lea et al, 2011;Ullrich et al, 2015;van der Zwaluw et al, 2014;Zacchia et al, 1991). Researchers have acknowledged the complicated nature of the results and have challenged the reliability of CHO effects on mood (Benton, 2002;Boyle et al, 2018;van de Rest et al, 2017).…”
Section: Carbohydrates and Mood: Mechanisms And Evidencementioning
confidence: 99%